The Ventral Striatum is a Key Node for Functional Recovery of Finger Dexterity After Spinal Cord Injury in Monkeys. (9th December 2019) - Suzuki, Michiaki; Onoe, Kayo; Sawada, Masahiro; Takahashi, Nobuaki; Higo, Noriyuki; Murata, Yumi; Tsukada, Hideo; Isa, Tadashi; Onoe, Hirotaka; Nishimura, Yukio
Abstract: In a recent study, we demonstrated that the ventral striatum (VSt) controls finger movements directly during the early recovery stage after spinal cord injury (SCI), implying that the VSt may be a part of neural substrates responsible for the recovery of dexterous finger movements. The VSt is accepted widely as a key node for motivation, but is not thought to be involved in the direct control of limb movements. Therefore, whether a causal relationship exists between the VSt and motor recovery after SCI is unknown, and the role of the VSt in the recovery of dexterous finger movements orfinger movements in general after SCI remains unclear. In the present study, functional brain imaging in a macaque model of SCI revealed a strengthened functional connectivity between motor-related areas and the VSt during the recovery process for precision grip, but not whole finger grip after SCI. Furthermore, permanent lesion of the VSt impeded the recoveryof precision grip, but not coarse grip. Thus, the VSt was needed specifically for functional recovery of dexterous finger movements. These results suggest that the VSt is the key node of the cortical reorganization required for functional recovery of finger dexterity.